(untitled) (International Nexus Multidisciplinary Research Journal, 2026)
Public debt and exports have a complex and often contradictory relationship with economic development in Nigeria. Public debt can stimulate short-term economic growth by funding infrastructure and development projects, but high debt burdens can also lead to unsustainable debt servicing, diverting resources from other vital sectors and hindering long-term growth. The main objective of the study is to analyze public debt, export, import and standard of living in Nigeria. The variables of external debt, domestic debt, oil export and non oil export were regressed on Per Capita Income. This study is anchored on Solow’s Growth Theory. Econometric technique involving Unit Root test and the Ordinary Least Square Regressions was used for data analysis. The result of the study revealed that external debt has negative and insignificant effect on per capita income in Nigeria. Domestic debt has significant effect on per capita income in Nigeria. Oil export has positive and significant effect on per capita income in Nigeria. Non oil export has significant effect on per capita income in Nigeria. The R2 of 76.645% and adjusted R2 of 72.58 indicate that the explanatory variables could exert a joint influence of 76.64% on the dependent variable, thus capable of coursing variations in the dependent variable. The study concludes that public debt and export has improved economic development in Nigeria: The study recommends that though debts are inevitable, especially for a developing nation like Nigeria, new debts should be incurred on the basis that most of the amounts should go into viable projects with a promising outlook of moving the nation from consumption to production. Policymakers/regulatory authorities in Nigeria should consciously analyze and examine fluctuations in the economy of countries on which they are dependent to prevent them from having a more adverse effect on the country’s economy. Industries in Nigeria should focus on building strong, independent, and flexible operational processes that are capable of adjusting to changes in the economic situation of the country and will prevent it from being heavily affected by the financial crisis. External debt should be contracted solely for short term investments with economic reasons and not for socio-political reasons or white elephant projects without economic justifications that can enhance human capital development in Nigeria. Government should avoid accumulation of unserviceable external debt stock overtime because it leads to debt overhang. Nigeria should use her foreign reserves instead of incurring more external debts, as this will ensure increase in real economic growth and reduce capital flights through repayments of debts to external sources.